Steroid Metabolome Analysis in Dichorionic Diamniotic Twin Pregnancy - Černý, Andrej; Hill, Martin; Vosátková, Michala; Laštůvka, Zdeněk; Pařízek, Antonín (International journal of molecular sciences, 2024)
Steroid hormones have diverse roles in pregnancy; some help stabilise pregnancy and influence the stability of pregnancy and the onset of labour. Changes and disorders in steroidogenesis may be involved in several pregnancy pathologies. To date, only a few studies have performed a very limited steroid analysis in multiple pregnancies. Our teams investigated multiple pregnancies regarding the biosynthesis, transport, and effects of steroids. We recruited two groups of patients: pregnant women with multiple pregnancies as the study group, and a control singleton pregnancies group. Blood samples were drawn from the participants and analysed. Information about the mother, foetus, delivery, and newborn was extracted from medical records. The data were then analysed. The gestational age of twin pregnancies during delivery ranged from 35 + 3 to 39 + 3 weeks, while it was 38 + 1 to 41 + 1 weeks for the controls. Our findings provide answers to questions regarding the steroidome in multiple pregnancies. Results demonstrate differences in the steroidome between singleton and twin pregnancies. These were based on the presence of two placentae and two foetal adrenal glands, both with separate enzymatic activity. Since every newborn was delivered by caesarean section, analysis was not negatively influenced by changes in the steroid metabolome associated with the spontaneous onset of labour.
Keywords: těhotenství s dvojčaty; Pregnancy, Twin; novorozenec; Infant, Newborn; výsledek těhotenství; Pregnancy; Humans; Infant; Metabolome; kojenec; Female; foetomaternal steroidome; Pregnancy Outcome; neuroactive steroids; pregnancy complications; lidé; steroidy; metabolom; ženské pohlaví; Cesarean Section; Retrospective Studies; multiple pregnancy; těhotenství; retrospektivní studie; Steroids; císařský řez